ANALYSIS OF SYNTACTIC ERRORS IN EXPOSITION CORRECTION OF CLASS X YAPIP SUNGGUMINASA HIGH SCHOOL GOWA DISTRICT - Musyawir, M. (Universitas Sembilanbelas November Kolaka, 2018)
The analysis of syntactic errors in exposition correction of class x class x YAPIP Sungguminasa high school Gowa district. The research objectives are: (i) to describe phrase errors found in studentsÃ¢Â€Â™ expository text of class X at SMA YAPIP Sungguminasa in Gowa Regency; and (ii) to describe sentence errors found in studentsÃ¢Â€Â™ expository text of class X at SMA YAPIP Sungguminasa in Gowa Regency. The study used qualitative descriptive design. Data collection techniques are techniques of reading, recording, and interviewing teachers and students. Data were analyzed by identifying, classifying, explaining, and evaluation. The results showed that (i) phrase errors include four types of prepositional phraseÃ‚Â errors, verbal phrase errors, nominal phrase errors, and adjective phrase error; (ii) Sentence errors include seven types: sentences have no subject, sentences have no subject and no predicate, illogical sentences, pleonasms, conjunctive disappearances, excessive conjunctions, and unnecessary usage of unquestioned words.